Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Penalaran Matematis Siswa SMP - Wahyuningsih, Dian; Utomo, Rukmono Budi; Warsito, Warsito (Universitas Muhammadiyah Palembang, 2022)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on students' mathematical reasoning abilities. The population in this study were all students of class VII MTs. Al-Hidayah. The sampling technique in this study was purposive sampling, in which the sample was taken with certain considerations. Then it was found that class VII A had 28 students as the experimental class and class VII B had 28 students as the control class. The research method used in this study is a quasi-experimental (quasi experiment research) with a nonequivalent group design type. The research design at this time used was to provide a pretest and also a posttest in the experimental class and control class. The research instrument used was a test of mathematical reasoning abilities on students, amounting to 5 questions in the description of which the instrument had been tested for validity and reliability. The results of the t-test on the posttest data of the experimental class that have been carried out with a significant level of 5% are obtained by the price of t_ (count)> t table (2.4892> 2.0048) so that H0 is rejected and H1 is accepted, which means that there is an effect of mathematical reasoning ability between students who are given the PBL learning model with those given the conventional learning model. Meanwhile, to determine the effect size of 0.67 with the classification of medium or medium. So it can be concluded that the PBL learning model has an influence on students' mathematical reasoning abilities